TERDAMPAKNYA PENDAPATAN PEDAGANG SAYURAN PADA MASA PANDEMI COVID-19 DI PASAR SHOPPING LIMBOTO KABUPATEN GORONTALO: - - Latif, Abdul; Mohamad, Roni; Murtini, Murtini; Mardiana, Andi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
This research sets out from the phenomenon of decreased income of greengrocers at the Limboto Shopping Market during the Covid-19 pandemic. The purpose of this research is to find out the impact of the Covid-19 pandemic on the greengrocers’ income at the Limboto Shopping Market, Gorontalo Regency. This research applies a qualitative approach. The greengrocers who become subjects in this research are those at the Limboto Shopping Market. The number of informants is 13 people of 22 greengrocers. Data collection involves observation, interview, and documentary techniques. Based on this research, it is found that the income of greengrocers at the Limboto Shopping Market during the pandemic has decreased because people's purchasing power has decreased, while the cost of living has increased. The decreased income has caused the greengrocers to consider whether to continue their business or not, taking into account that there is no reduced fare in the payment for the rental stalls. In addition, the absence of intensive handling causes the business to be threatened with closure and the capital runs out so that traders suffer losses. On the other hand, there is a government policy regarding limiting operating hours which causes an unstable economic cycle.